Recent progress in gut microbiota - Danying Cheng; Huichun Xing (Gastroenterology & Endoscopy, 2023)
There are hundreds of millions of microorganisms in the human intestines, and the unity of the interaction between intestinal microbiota and their hosts is called intestinal microecology. Intestinal microecology involves in many physiological processes, such as metabolism and immune regulation, directly affecting human health. Besides digestive tract diseases, the imbalance in intestinal microecology has also been identified as closely associated with the occurrence and development of liver diseases, tumors, cardiovascular diseases, metabolic-related diseases, and neurological and psychiatric diseases. Microecological therapeutic strategies targeting intestinal microbiota are a potential novel treatment for various chronic diseases. This paper reviewed the research progress in intestinal microecology in recent years.